Anti–PD-1 and Anti–PD-L1 in Head and Neck Cancer: A Network Meta-Analysis - Botticelli, Andrea; Cirillo, Alessio; Strigari, Lidia; Valentini, Filippo; Cerbelli, Bruna; Scagnoli, Simone; Cerbelli, Edoardo; Zizzari, Ilaria Grazia; Rocca, Carlo Della; D’Amati, Giulia; Polimeni, Antonella; Nuti, Marianna; et al. (Frontiers in Immunology, 2021)
Objective The monoclonal antibodies anti-programmed death protein-1 (anti PD-1) nivolumab and pembrolizumab are the first immune checkpoint inhibitors (ICIs), approved for treatment of recurrent/metastatic head and neck carcinoma R/M HNSCC in first line and in platinum refractory disease. This network meta-analysis aims to investigate the efficacy of anti-PD-1 vs anti-PD-L1 based therapy in R/M HNSCC cancer patients through a systematic review of the literature in order to provide support for evidence-based treatment decisions. In particular the effectiveness of ICIs for R/M HNSCC is analysed according to the different mechanisms of action of the check-points inhibitory drugs in different subgroups of patients. Materials and Methods: We did a systematic literature review and network meta-analysis (NMA) of randomized controlled trials (RCTs) in PubMed, ClinicalTrials.gov, Embase, Medline, the Cochrane Central Register of Controlled Trials, Web of Science. Our search identified a total of 5 randomized controlled trials: Keynote 040, Keynote 048, Eagle, Condor, Checkmate 141. These trials included 3001 patients. Treatment was sub-categorized into PD-L1-based, PD-1-based and standard chemotherapy. Treatments were indirectly compared with anti PD-L1 based therapy. Results: The network meta-analysis demonstrated no significant differences in OS between different subgroups except for the metastatic patients in which anti PD-1 based therapy was associated with significantly less risk of death. Furthermore, anti-PD-1 based therapy appeared to be effective in smoker patients and in human papilloma negative (HPV) patients. Conversely anti PD-L1 based therapy seems to be better efficient in female patients, in locally recurrent setting and in HPV positive patients. Conclusion: This is the first NMA study aimed to indirectly comparing anti PD-1 and anti PD-L1 based therapy in HNSCC patients. The results of our NMA could help to define a profile of patient responder or resistant to specific classes of immune drugs and can be used to guide/design future studies in the novel scenario of precision immune-oncology.